Given $$(m-2)x^2-4x+3=3-x^2+2nx$$ Compute the value of $m$.

$$(m-2)x^2-4x+3=3-x^2+2nx \\mx^2+(-4m-4)x+7=-x^2+2nx+3 \\m=-1, n=0$$

The answer is $m=1,n=-2$, please tell me where did I go wrong

  • 3
    $\begingroup$ There is no linear term in $(m-2)x^2$, it's purely quadratic in $x$. $\endgroup$ – lulu Sep 23 '18 at 13:38


The coefficient of $x^2$ on the left of the equal sign is $(m-2)$ and on the right it is $-1$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.